Deltamethrin ingestion with suicidal intent: A fatal outcome - Varun Kaul; Ghanshyam Saini; Sandesh Ganjoo; Anumodan Gupta; Sunil Kumar Raina (Wolters Kluwer Medknow Publications, 2015)
Deltamethrin intoxication is uncommon throughout the globe and more so the oral ingestion. The toxicity of pyrethroids is considered much less than the intoxication caused by other insecticides, especially organophosphates. This report describes a case of a 14-year-old female child who was admitted to the emergency room (ER) with dyspnea, cyanosis, tetany, seizures and coma following deltamethrin ingestion in a suicidal attempt. Deltamethrin ingestion should be considered as a differential diagnosis in patients presenting to ER with nonspecific neurological symptoms.